Faktor pendukung dan penghambat penerapan pedoman gizi klinik di rumah sakit: Scoping review - Ibnamuthi, Uray Cassandra; M, Kartasurya; T, Purnami C. (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Clinical nutrition guidelines aim to enhance the quality of nutritional care and support evidence-based practices in hospitals. However, their implementation faces multiple challenges at systemic, institutional, and individual levels. Globally, malnutrition affects 20% to 50% of hospitalized patients and contributes to higher mortality, prolonged hospital stays, and increased healthcare costs. Despite these consequences, integration of nutrition guidelines into routine hospital practice remains limited.Objective: This scoping review aims to identify and map the factors that influence the implementation of nutrition guidelines in hospitals based on global scientific literature published in the last five years.Methods: A scoping review was conducted using the PEO (Population, Exposure, Outcome) framework. Articles were identified through Scopus, EBSCOhost, and PubMed, focusing on open-access English-language publications from 2020 to 2025 discussing facilitators and barriers to hospital nutrition guideline implementation. Following PRISMA-ScR procedures, 25 eligible studies were included and analyzed thematically.Results: A total of 5,760 articles were identified. After screening and eligibility assessment, 25 studies were included in the synthesis. Key enablers were staff training, digital systems, teamwork, supportive policies, and patient education. Main barriers included limited dietitian involvement, poor system integration, inadequate training, administrative issues, and logistical constraints.Conclusion: The implementation of clinical nutrition guidelines is shaped by a complex interplay of supportive and obstructive factors. Enhancing success requires comprehensive, system-based strategies focusing on training, policy alignment, team communication, and digital integration tailored to institutional contexts.